Improving the stellarator through advances in plasma theory. (2nd February 2022) - Hegna, C.C.; Anderson, D.T.; Bader, A.; Bechtel, T.A.; Bhattacharjee, A.; Cole, M.; Drevlak, M.; Duff, J.M.; Faber, B.J.; Hudson, S.R.; Kotschenreuther, M.; Kruger, T.G.; et al.
Abstract: Improvements to the stellarator concept can be realized through advancements in theoretical and computational plasma physics. Herein, recent advances are reported in the topical areas of: (1) improved energetic ion confinement, (2) the impact of three-dimensional (3D) shaping on turbulent transport, (3) reducing coil complexity, (4) novel optimization and design methods, and (5) computational magnetohydrodynamic tools. These advances enable the development of new stellarator configurations with improved confinement properties.